The United Arab Emirates : an economic and social survey - Fenelon, K. G. (London ; New York : Longman, 1973)
The book gives the historical background, foundation and the economic aid and development of the United Arab Emirates.
Includes index.
Includes bibliographical references: p. 157.
rpm 19/06/2017
Loans
Keywords: United Arab Emirates--Economic conditions; United Arab Emirates. $1 (BConstitution $1 (BEconomic conditions.s; United Arab Emirates -- Social conditions; Economic history; Social conditions .; United Arab Emirates